Relational Epistemology in the Social Sciences: Pierre Bourdieu’s Epistemological Legacy - Gürhan Özpolat (Skad)
The distinction between subjectivist and objectivist approaches has persisted as a fundamental dichotomy in sociological theory for many years. Pierre Bourdieu’s epistemological sociology challenges these opposing approaches and aims to overcome the artificial dichotomies that have long plagued the social sciences. In this article, we argue that Bourdieu opens a third epistemological path, effectively ending the conflict between objectivism and subjectivism that has divided the social sciences into two poles. To achieve this, we explore the influence of the French historical epistemological tradition on Bourdieu's sociological production, emphasizing the importance of recognizing this tradition in shaping Bourdieu’s sociological theory. After clarifying the basic epistemological principles that scientifically grounded sociological studies should follow, we delve into Bourdieu’s critique of subjectivism and objectivism. Finally, we emphasize the importance and potential of adopting Bourdieu’s relational epistemology, which he proposes to do away with essentialist thinking.